Mentoring Programmes: Supporting Effective Technology Use in Transparency and Accountability Organisations - and Herringshaw, Vanessa; Faith, Becky (Transparency & Accountability Initiative, 2015)
The global movement to hold governments and companies accountable is growing rapidly, and technology can play a vital role. Some actors harness this potential to brilliant effect. But many others waste precious money and staff time on technology that isn’t a good fit for their aims or capacity. Mentorships can be a really effective way …